Patterns of new firm Survival and Growth in the Italian Financial Intermediation Industry - Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
This paper studies the post-entry evolution of two cohorts of entrants in the Italian financial intermediation industry. Using a comprehensive longitudinal database, it analyses the link between duration and growth of each newborn firm and its start-up size, as well as a series of industry-specific characteristics. It emerges that not only did regulatory reform in 1990 result in a process of branch proliferation and industry consolidation, but it also set in motion a pre-entry selection mechanism and rendered life after entry for newborn firms more difficult. Conversely, before completion of the regulatory reform, in 1989, entry was possible even for very small firms, and larger new entrants were able to resist longer periods of bad performance than their smaller counterparts before being forced to exit the market, and this independently of the features of spatial and structural competition.
Keywords: 330